A new species of the genus Thalassaphorura from East China (Collembola: Onychiuridae) - Yan, Haijuan; Shi, Shidi; Chen, Jianxiu (Zootaxa, 2006)
A new onychiurid species, Thalassaphorura qixiaensis sp. nov., is reported from Jiangsu Province of East China. Morphologically, it is very similar to the widely-spread and definitely parthenogenetic species Th. encarpata (Denis, 1931). The new species is gamogenetic and differs from the latter in labial palp and proximal setae. A key to the Chinese species of the genus is given.